TEACHING TOOLS BASED ON PEDAGOGICAL TECHNOLOGIES (Ta'limning zamonaviy transformatsiyasi, 2024)
At the same time, many methods of using information and communication technologies in physics lessons and the effectiveness of these methods are analyzed. Ensuring the acquisition of skills in the study of science, the formation of hypotheses, design, conducting experiments, evaluating the results obtained, developing skills for the safe and effective use of laboratory equipment, accurate measurements and the adequacy of the assessment of the level of results obtained, based on an interdisciplinary analysis of educational tasks, in order to provide scientifically based evidence of their action.The article is intended for teachers working in the direction of "Physics", and students studying in the direction of "Physics".